2008
DOI: 10.1108/10748120810912501
|View full text |Cite
|
Sign up to set email alerts
|

Publishing, ranking, and the future of heterodox economics

Abstract: PurposeThe purpose of the “Introduction” is to provide the motivation and context for the articles of this special issue and an overview and summary of the contributions that follow.Design/methodology/approachThe paper provides an overview and summary of the contributions in the special issue.FindingsIt is argued that heterodoxies had gained a considerable and growing influence on research orientations, methodologies, and critical reflections, also on the mainstream publishing practices, even in the mainstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
(14 reference statements)
0
20
0
Order By: Relevance
“…However, in none of the articles do the supporters actually provide any evidence-names of heterodox economists and their actions, policies of current heterodox associations and journals, or decisions made by heterodox economic departments-that support the charge of anti-pluralism and intolerance.20 The basis for this claim is found inLee (2006Lee ( , 2009 andLee and Elsner (2008).at TEXAS SOUTHERN UNIVERSITY on October 11, 2014 rrp.sagepub.com Downloaded from…”
mentioning
confidence: 86%
“…However, in none of the articles do the supporters actually provide any evidence-names of heterodox economists and their actions, policies of current heterodox associations and journals, or decisions made by heterodox economic departments-that support the charge of anti-pluralism and intolerance.20 The basis for this claim is found inLee (2006Lee ( , 2009 andLee and Elsner (2008).at TEXAS SOUTHERN UNIVERSITY on October 11, 2014 rrp.sagepub.com Downloaded from…”
mentioning
confidence: 86%
“…Central to such game playing are efforts to define and legitimize preferentially rewarded research space (see Marsden, 1993;Bedeian, 2004). So, for example, to the extent that a list elevates an established, North American-dominated, set of journals as 6 the benchmark of `top-notch' research, a particular, neo-positivist research agenda is deemed to yield the highest `quality' publications (see, for example, Lee and Elsner, 2008).…”
mentioning
confidence: 99%
“…When we did the introduction of a special issue of On the Horizon in 2008, we disagreed with some critical economists like S. Dow, J. Davis, T. Lawson, R. Backhouse, and D. Colander who suggested that there is and will be more pluralism emerging in economics and that the mainstream somehow is fragmenting and dissolving (as cited in Lee/Elsner 2008). Our pessimistic view of an ongoing counterattack, in contrast, was based on the fact that even a relative dominance of heterodoxy in terms of research questions, approaches, and methodologies over the last, say, 25 years would have not spilled over into the areas of funding and recruitment for heterodox economists, of the curricula of mass teaching and the advice business, and would leave untouched the mainstream's and its allies' general world view.…”
Section: Forummentioning
confidence: 96%
“…Countless other critical declarations of economists have come out since the burst of the giant fi nancial bubble. One shall just be mentioned: David Colander, Hans Foellmer, Alan Kirman and other wellknown complexity and evolutionary economists have launched the so called Dahlem-Report in February 2009, ›Th e Financial Crisis and the Systemic Failure of Academic Economics.‹ Despite these severe and fundamental failures, over the last three decades the ruling forces of mainstream economics and their allies in politics, public administration and in the organizations of big business utilize rankings as a power device to rule, to direct research funds to their own ranks, to make or destroy careers of critical economists, to up-and downgrade journals and departments, and, particularly, to elbow out of academic research, teaching, and advice their potential competitors of the diverse heterodox approaches (Lee/Elsner 2008, Lee 2009, Butler 2010, Katzner 2010.…”
Section: Forummentioning
confidence: 99%